Pengaruh Earning Per Share dan Price to Book Value terhadap Harga Saham Pada PT. Indofood CBP Sukses Makmur, Tbk - irnawati, Jeni; Wirawan Suryanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of This study to find out the impact of Earning Per Share (EPS) and Price to Book Value (PBV) to the stock price of PT. Indofood CBP Sukses Makmur, Tbk period of 2010-2019. Quantitative approach is used to find and analyze the impact of Earning Per Share (EPS) and Price to Book Value (PBV) variables through the stock value simultaneously or partially, and to find out which variables provide the most dominant to the stock price of PT. Indofood CBP Sukses Makmur, Tbk. Based on The Test Result of Simple Linear Regression, Multiple Linear Regression, and Determination Coefficients show that the variable influence strongly to the price stock, in Partial Test (T Test) variable Earning Per Share (PBV) is unrelated and not significant on stock prices and Price to Book Value (PBV) associated with and significant to stock prices. The test result between EPS and PBV on the stock prices of PT. Indofood CBP Sukses Makmur, Tbk using the Runs Test proves that there is no autocorrelation in this study, and based on the Simultaneous Test, both variables can be concluded as Earning Per Share (EPS) and Price to Book Value (PBV) together with as important and significant to the stock price of PT. Indofood CBP Sukses Makmur, Tbk